Analysis of the social and media debate during the Catalan Independence Referendum - Zamora-Medina, Rocío; García-Jiménez, Leonarda (Brazilian journalism research, 2022)
ABSTRACT – This research includes an analysis of the media frameworks built around the Catalan government’s attempt to organize the referendum for independence from Spain on Oct 1st, 2017. Based on previous studies on the use of pragmatic and symbolic frameworks during independence processes, the objective is to identify the main interpretive frameworks, actors, and actions that starred in the symbolic battle over national identities, comparing (1) the media coverage of the referendum in two national, two international, and two regional newspapers with (2) the social debate on Twitter. The comparative quantitative analysis shows how the media prioritized emotional information and historical aspects, with notable differences between the national media and the social debate on Twitter. The coverage in international newspapers, however, was more similar to the debate on Twitter and had a notable influence on framing this public issue. RESUMO – Esta pesquisa inclui a análise das estruturas de mídia construídas em torno da tentativa do governo catalão de organizar o referendo pela independência da Espanha em 1º de outubro de 2017. Com base em estudos anteriores sobre o uso de estruturas pragmáticas e simbólicas em processos de independência, o objetivo é identificar os principais marcos interpretativos, atores e ações que protagonizaram a batalha simbólica pelas identidades nacionais, comparando (1) a cobertura midiática do referendo em dois jornais nacionais, dois internacionais e dois regionais com (2) a conversa social no Twitter. A análise quantitativa comparativa ilustra como a mídia priorizou a informação emocional e os aspectos históricos, com diferenças notáveis ​​entre a mídia nacional e a conversa do Twitter. Jornais internacionais, no entanto, foram mais parecidos com a conversa no Twitter e tiveram uma influência notável no enquadramento desta questão pública. RESUMEN – Esta investigación incluye el análisis de los marcos mediáticos construidos alrededor del intento del gobierno catalán de organizar el referéndum de independencia de España del 1-Oct de 2017. Basado en estudios previos sobre el uso de marcos pragmáticos y simbólicos en los procesos de independencia, el objetivo es identificar los principales marcos interpretativos, actores y acciones que protagonizaron la batalla simbólica sobre las identidades nacionales, comparando (1) la cobertura mediática del referéndum en dos diarios nacionales, dos internacionales y dos regionales con (2) la conversación social en Twitter. El análisis cuantitativo comparativo ilustra cómo los medios priorizaron la información emocional y los aspectos históricos, con notables diferencias entre los medios nacionales y la conversación de Twitter. Los diarios internacionales, sin embargo, fueron más similares a la conversación en Twitter y tuvieron notable influencia en el enmarcado de este tema público.